Responsible Leadership and Village Apparatus Performance: The Moderating Role of Village Development Status - Khairun A. Roni; Ari Pramono; Amran Amran; Supriyati Supriyati; Ida Zuliyana (Business and Applied Management Journal, 2026)
Responsible leadership has been associated with positive employee outcomes, yet little is known about its effectiveness across different governance contexts, particularly in village governments. This study investigates how responsible leadership influences village apparatus performance through work motivation and examines the moderating role of village development status. A quantitative survey was conducted among 300 village apparatus from 60 villages in Bungo Regency, Indonesia, using stratified random sampling. Data were collected through a three-wave survey design to reduce common method bias and analyzed using Hayes' PROCESS Model 7. The results show that responsible leadership positively affects village apparatus performance both directly (B = 0.24, p < .001) and indirectly through work motivation (indirect effect = 0.16, 95% CI [0.10, 0.23]). Village development status significantly strengthens the relationship between responsible leadership and work motivation, producing stronger indirect effects in Self-reliant and Advanced villages. This study extends responsible leadership research by demonstrating that governance maturity serves as a contextual boundary condition for leadership effectiveness in village governments. The findings suggest that leadership development should be aligned with village development status and supported by governance capacity-building initiatives.